Analisis Efektivitas Pemberian Umpan Balik dalam Pembelajaran Mikro pada Mahasiswa Program Studi Pendidikan Bahasa Inggris Semester VII UIN Jakarta - Kandradiansyah Hadis Purwadiman Aditya Tribuana Chandraca Satya Dharma; Alyssa Puri Nadira; Muhammad Hafizh Alfatih Nadira; Wahyunengsih Wahyunengsih (Universitas Muhammadiyah Ponorogo, 2026)
This study investigated the effectiveness of feedback in Microteaching classes among seventh-semester English Education students at UIN Syarif Hidayatullah Jakarta. Employing a mixed-method approach integrating classroom observations, questionnaires, and interviews, the research aimed to explore how feedback influenced students’ teaching performance, reflective learning, and professional development. Sixteen students participated in the questionnaire, and three students were interviewed to provide in-depth insights. The findings revealed that feedback significantly improved instructional clarity, classroom management, and learning engagement. Specific, constructive, and reflective feedback helped students identify weaknesses in lesson planning, adjust teaching strategies, and enhance confidence in their instructional delivery. Supportive and non-judgmental feedback, including peer interactions, reduced anxiety and promoted active participation. Students preferred guided and discussion-based feedback over direct correction alone, which aligned with sociocultural principles of scaffolded learning. Despite generally positive perceptions, challenges were noted, such as vague feedback or inconsistent corrective guidance. Overall, the study highlights the critical role of feedback in bridging theoretical knowledge and practical teaching skills, emphasizing the importance of clarity, emotional sensitivity, and structured delivery. The research provides practical implications for teacher educators, suggesting strategies for enhancing both lecturer and peer feedback to foster reflective, competent, and confident pre-service English teachers.